2012
DOI: 10.1242/dev.077347
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin and AP-1 regulate apical polarity and lumen formation duringC. eleganstubulogenesis

Abstract: SUMMARYClathrin coats vesicles in all eukaryotic cells and has a well-defined role in endocytosis, moving molecules away from the plasma membrane. Its function on routes towards the plasma membrane was only recently appreciated and is thought to be limited to basolateral transport. Here, an unbiased RNAi-based tubulogenesis screen identifies a role of clathrin (CHC-1) and its AP-1 adaptor in apical polarity during de novo lumenal membrane biogenesis in the C. elegans intestine. We show that CHC-1/AP-1-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
105
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(120 citation statements)
references
References 55 publications
12
105
0
Order By: Relevance
“…Several hypotheses can be proposed for AP-1 function in apical trafficking. First, AP-1 could be implicated solely in basolateral targeting followed by transcytosis of apical proteins; we do not favour this hypothesis because preventing endocytosis by targeting dynamin should allow us to see apical cargos at the basolateral membrane, something we did not observe [see also accompanying paper (Zhang et al, 2012)]. Alternatively, AP-1 could target a factor to the basolateral membrane, which would be required to exclude apical proteins; in the early embryo, the RhoGAP PAC-1 excludes CDC-42 and PAR-6 from cell-cell contact and its absence leads to a lateral localisation of these two proteins (Anderson et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…Several hypotheses can be proposed for AP-1 function in apical trafficking. First, AP-1 could be implicated solely in basolateral targeting followed by transcytosis of apical proteins; we do not favour this hypothesis because preventing endocytosis by targeting dynamin should allow us to see apical cargos at the basolateral membrane, something we did not observe [see also accompanying paper (Zhang et al, 2012)]. Alternatively, AP-1 could target a factor to the basolateral membrane, which would be required to exclude apical proteins; in the early embryo, the RhoGAP PAC-1 excludes CDC-42 and PAR-6 from cell-cell contact and its absence leads to a lateral localisation of these two proteins (Anderson et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…We therefore propose that a SOAP-1/AP-1/clathrin module controls E-cad apical sorting in the epidermis. In the intestine, AP-1 is also required for apical sorting but triggers a very different phenotype in which the lateral membrane is converted into an apical membrane (Shafaq-Zadah et al, 2012;Zhang et al, 2012). Interestingly, we observed that E-cad is lateral in the intestine of larvae and not missorted upon AP-1 depletion, whereas the loss of soap-1 had no effect on the localisation of PAR-6 (Shafaq-Zadah et al, 2012) or CDC-42 (G.G.…”
Section: Discussionmentioning
confidence: 99%
“…The AP-1 functions identified in neurons (Dwyer et al, 2001) or in the intestine (Shafaq-Zadah et al, 2012;Zhang et al, 2012) cannot account for this lethality. At the developmental level, embryonic elongation requires seam cell elongation driven by actin tension in epidermal cells and functional muscles attached to the epidermis from twofold stage (Chisholm and Hardin, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the AP-1 clathrin adaptor (known as APS-1 in C. elegans) is required for actin organization and apical targeting of several proteins including the polarity factor PAR-6 and E-cadherin (Gillard et al, 2015;Shafaq-Zadah et al, 2012;Zhang et al, 2012). Third, loss of APS-1 induces ectopic mini-intestinal lumen also observed after the loss of the cytosolic chaperonin CCT-1 (also known as TCP-1), which affects both the actin and MT filaments (Saegusa et al, 2014;Shafaq-Zadah et al, 2012;Zhang et al, 2012).…”
Section: Fig 2 Mt and Mt-related Motors During Nuclear Migration Ormentioning
confidence: 99%